Signs & shrines : spiritual journeys across New Mexico - Niederman, Sharon (Woodstock, VT : Countryman Press, 2012)
New Mexico's silent landscape with its vast stretches of open sky above uninhabited desert elicits a spiritual response from residents and travelers alike. Spend time here and you will encounter many spiritual markers, from Spanish mission churches built atop ruins of Native American kivas to bathtub virgins. Mosques and temples augment the diverse harmony. Faith and practice have created a special atmosphere here, making the sacred more accessible. Now, with "Signs & Shrines", sacred sites are more accessible than ever.
Includes index.
Keywords: Sacred space -- New Mexico; Shrines -- New Mexico; Indians of North America -- New Mexico; New Mexico; New Mexico -- Description and travel; New Mexico -- Religious life and customs